Differential methylation of the HPV 16 upstream regulatory region during epithelial differentiation and neoplastic transformation - Vinokurova, Svetlana; Knebel Doeberitz, Magnus von (PLOS ONE, 2011)
High risk human papillomaviruses are squamous epitheliotropic viruses that may cause cervical and other cancers. HPV replication depends on squamous epithelial differentiation. Transformation of HPV-infected cells goes along with substantial alteration of the viral gene expression profile and preferentially occurs at transformation zones usually at the uterine cervix. Methylation of the viral genome may affect regulatory features that control transcription and replication of the viral genome. Therefore, we analyzed the methylation pattern of the HPV16 upstream regulatory region (URR) during squamous epithelial differentiation and neoplastic transformation and analyzed how shifts in the HPV URR methylome may affect viral gene expression and replication. HPV 16 positive biopsy sections encompassing all stages of an HPV infection (latent, permissive and transforming) were micro-dissected and DNA was isolated from cell fractions representing the basal, intermediate, and superficial cell layers, each, as well as from transformed p16INK4a-positive cells. We observed fundamental changes in the methylation profile of transcription factor binding sites in the HPV16 upstream regulatory region linked to the squamous epithelial differentiation stage. Squamous epithelial transformation indicated by p16INK4a overexpression was associated with methylation of the distal E2 binding site 1 leading to hyper-activation of the HPV 16 URR. Adjacent normal but HPV 16-infected epithelial areas retained hyper-methylated HPV DNA suggesting that these viral genomes were inactivated. These data suggest that distinct shifts of the HPV 16 methylome are linked to differentiation dependent transcription and replication control and may trigger neoplastic transformation.